THE ROLE OF ENGLISH LANGUAGE EDUCATION IN SOCIAL MEDIA-BASED MARKETING STRATEGIES AND GLOBAL TRENDS: DIGITAL ETHNOGRAPHY STUDY - Muhamad Alfi Khoiruman; Doni Hadi Irawan; Fandi Ahmad (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
This study examines the role of English language education in shaping social media–based marketing strategies within the context of global trends. In the era of digital globalization, English has become a strategic competence that influences how brands communicate, construct identities, and engage audiences across borders. The purpose of this research is to explore how English language proficiency, acquired through formal and informal education, is utilized by digital marketers in designing content, narratives, and interactions on social media platforms. This study employs a qualitative approach using digital ethnography, with data collected through online observations, in-depth interviews, and analysis of social media content across platforms such as Instagram, TikTok, and YouTube. The findings reveal that English language education plays a significant role not only as a communication tool but also as a cultural and symbolic resource that enhances brand credibility, global appeal, and trend alignment. The study concludes that English language education contributes strategically to contemporary marketing management by enabling marketers to adapt to global trends while maintaining local relevance, highlighting the need for integrative language education aligned with digital marketing practices.